Overview of tau PET molecular imaging. Issue 2 (21st April 2022) - Cassinelli Petersen, Gabriel; Roytman, Michelle; Chiang, Gloria C.; Li, Yi; Gordon, Marc L.; Franceschi, Ana M.
Abstract : Purpose of review: This article reviews tau PET imaging with an emphasis on first-generation and second-generation tau radiotracers and their application in neurodegenerative disorders, including Alzheimer's disease and non-Alzheimer's disease tauopathies. Recent findings: Tau is a critical protein, abundant in neurons within the central nervous system, which plays an important role in maintaining microtubules by binding to tubulin in axons. In its abnormal hyperphosphorylated form, accumulation of tau has been linked to a variety of neurodegenerative disorders, collectively referred to as tauopathies, which include Alzheimer's disease and non-Alzheimer's disease tauopathies [e.g., corticobasal degeneration (CBD), argyrophilic grain disease, progressive supranuclear palsy (PSP), and Pick's disease]. A number of first-generation and second-generation tau PET radiotracers have been developed, including the first FDA-approved agent [ 18 F]-flortaucipir, which allow for in-vivo molecular imaging of underlying histopathology antemortem, ultimately guiding disease staging and development of disease-modifying therapeutics. Summary: Tau PET is an emerging imaging modality in the diagnosis and staging of tauopathies.